2009
DOI: 10.1007/s11666-009-9307-4
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanism for Thermal Fatigue of Thermal Barrier Coating Systems

Abstract: Thick thermal barrier coatings (TBCs), consisting of a CoNiCrAlY bond coat and yttria-partially stabilized zirconia top coat with different porosity values, were produced by air plasma spray (APS). The thermal fatigue resistance limit of the TBCs was tested by furnace cycling tests (FCT) according to the specifications of an original equipment manufacturer (OEM). The morphology, residual stresses, and micromechanical properties (microhardness, indentation fracture toughness) of the TBC systems before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 39 publications
3
21
1
Order By: Relevance
“…Beginning of the failure from the edges was due to the extreme heating and cooling conditions encountered and the singularity of thermal stresses at the edges. Other studies [4,26,27] have also mentioned the edge effect on failure during thermal cycling. Figure 6 presents the weight changes as a function of cycle number for three kinds of nanostructured samples during thermal shock testing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beginning of the failure from the edges was due to the extreme heating and cooling conditions encountered and the singularity of thermal stresses at the edges. Other studies [4,26,27] have also mentioned the edge effect on failure during thermal cycling. Figure 6 presents the weight changes as a function of cycle number for three kinds of nanostructured samples during thermal shock testing.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [27][28][29] showed that oxidation of the bond coat and thermal mismatch stress were the main factors causing degradation of TBCs. EDS analyses of top coat/bond coat interfaces of the three nanostructured TBCs after thermal shock testing are shown in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique of indentation fracture toughness measurement, described in detail by Ponton and Rawlings [13], can be successfully used for evaluation of thick brittle coatings [14][15][16]. In this case, the model of Lawn and Swain [17] was used to determine the number of K Ic .…”
Section: Indentation Fracture Toughnessmentioning
confidence: 99%
“…The pores in a plasma-sprayed coating can be divided into three types with various orientations and shapes: intra-lamellar cracks, inter-lamellar pores and globular pores [7][8][9]. In addition, the pore structure of the coating may evolve during the thermal cycling due to the effect of sintering and thermal stress [10,11]. The increase in stiffness caused by the sintering of fine-scale porosity has significant impact on the strain tolerance of the TBC [12].…”
Section: Introductionmentioning
confidence: 99%